The evolution of non-traditional workplaces: from third places to hybrid places - Tomaz, E.; Helyaneh (Evolution of New Working Spaces. Changing Nature and Geographies, 2024)
Recent socioeconomic and technological developments with significant impacts on work organization and labor relations, along with changes in the work/life relationship, have driven the emergence and rapid growth of new working spaces (NeWSps). Starting with a review of the multidisciplinary literature, we seek to identify and understand the various categories and related concepts arising from non-traditional workspaces and their evolution. Concepts such as “third place” as an alternative to home (“first place”) and workplaces of production (“second place”) refer to environments that facilitate informal social relations and provide a sense of community. Alongside the emergence of third places for work, discussions about hybrid places are arising as a spatial concept that combines two or more predefined NeWSps typologies, either with each other or with inherently tourism and hospitality infrastructure. The typologies presented serve as analytical tools to improve the understanding of this growing phenomenon, foster its diversity and integration, and contribute to future research on NeWSps and their socioeconomic implications.